Comprehensive Risk Assessment of Metals and Minerals in Seafood Using Bioaccessibility Correction - Ștefania-Adelina Milea; Ira-Adeline Simionov; Nina-Nicoleta Lazăr; Cătălina Iticescu; Mihaela Timofti; Puiu-Lucian Georgescu; Caterina Faggio (Journal of Xenobiotics)
Evaluating the bioaccessibility and health risks of seafood is extremely important because, although it is a significant source of vital minerals, it may also contain potentially toxic elements. This study aimed to determine the content of metals and minerals in different seafood species before and after thermal processing. Also, given the risk of overestimating the actual final concentration available in the body, a study was carried out to determine the bioaccessibility of these elements by simulating the digestion process in the gastrointestinal tract. Assessment of the potential toxic effects on consumer health in terms of exposure to heavy metals was carried out through risk analysis by Estimated Daily Intake, Hazard Index, and Cancer Risk parameters. Three bivalve mollusks, one gastropod mollusk, four cephalopod mollusks, and one crustacean species were analyzed in terms of minerals (P, S, K, Ca, and Se) and heavy metals (Cd, Pb, Ni, Cr, Fe, Zn, Co, Mn, and As) content. The lead (Pb) concentration recorded the strongest bioaccessibility increase, even reaching 100% in P. vannamei. Generally, the bioaccessibility of all metalloids dropped below 100%, which suggests that only a part of the amount of metal in the initially ingested sample can be absorbed by the human organism. Potassium and sulfur registered the greatest value, up to 23% for minerals’ bioaccessibility in the same samples. The highest intake rate of metals occurred after the consumption of M. gigas, which registered the highest Estimated Daily Intake for Cr (chromium) (0.321 mg kg−1 d−1), Cu (copper) (10.15 mg kg−1 d−1), and Zn (zinc) (12.67 mg kg−1 d−1). The Hazard Index values indicated no significant risk of poisoning. All calculated Cancer Risk scores remained below the acceptable threshold. Moreover, the Pearson coefficient revealed a positive correlation between the Hazard Index and the most abundant elements in the samples, Cr, Zn, and Cu. This study could provide a framework for evaluating both the nutritional benefits and toxicological concerns of seafood intake in public health applications.